Correlation of Inappropriate use of Ceftriaxone and Bacterial Resistance in the Hospital Environment: Integrative Review - Abrantes, Larissa Furtado; de Sousa, Joyce Lima; Ramos, Joel Messias Soares; Leite, Rafael Rodrigues; Ferreira, Sávio Benvindo (Archives of Pharmacy and Pharmaceutical Sciences, 2024)
Introduction: Bacterial resistance is a threat to public health, as it is estimated that 37,000 people die due to hospital infections, most of them due to multidrug-resistant bacteria. In part, this resistance is due to the inappropriate use of antibiotics, with ceftriaxone being one of the most used. Therefore, this article aims to analyze the consequences of using ceftriaxone in the hospital environment. Methodology: This is an integrative qualitative review, following the PICO strategy, using the Embase, BVS, and Pubmed databases, with the guiding question being: “In patients admitted to a hospital environment (P), is ceftriaxone used appropriately (I) for the treatment of infections (CO)?” and the time frame from 2013 to 2023. Results: 272 articles were found in total, 46 obtained from the VHL, 62 from PubMed, and 164 from Embase. Of these, 66 were duplicates, leaving 206 works for title and summary reading. After reading, 79 were selected for full reading, with 7 articles ultimately being selected for the study. An average of 62.3% of inappropriate use was found, with the minimum value found being 19% and the maximum being 87.9%. The main reasons for this use were: indication, dose, frequency, and duration. Conclusion: From reading the articles, it is concluded that the inappropriate use of ceftriaxone is mainly due to: indication, dose, frequency, and duration of treatment. These elements must be monitored, as their inappropriate use increases the length of hospital stay and may be associated with the emergence of bacterial resistance.